20 years (2004-2024) exploring research trend in intellectual disabilities towards inclusion: a bibliometric study - Saini, Rosnani; Nordin, Zaimuariffudin; Hashim, Mohd Hafizan; Abol, Mohamad Taha (Intelektual Pustaka Media Utama, 2025)
This study presents a comprehensive bibliometric analysis of intellectual disabilities education towards inclusion research from 2004 to 2024. Using the Scopus database and VOSviewer software, we analyzed 1,562 articles to identify research trends, key contributors, and emerging themes. The results reveal a significant increase in publication output over the two decades, with the highest number of publications occurring in 2022. Major themes include inclusive practices, special education approaches, and social aspects of disability. Keyword analysis highlighted the field's multidisciplinary nature, integrating educational, psychological, and healthcare perspectives. Co-authorship networks showed strong collaboration among Western countries, indicating potential for expanded global partnerships. The study concludes that future research should focus on underrepresented areas such as assistive technology and rare disorders, while expanding international collaborations. This overview provides valuable insights for researchers and practitioners, emphasizing the need for diverse perspectives to enhance the global impact of intellectual disabilities education towards inclusion.